(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted in the Jordanian Bashair project,River Nile State, during two seasons (2007 and 2008) to evaluate theperformance of irrigation systems applying different amounts of irrigationwater. The treatments were surface irrigation method (basin irrigationsystem) and localized irrigation system with two types of distributors:locally made bubblers and imported bubblers. The irrigation wateramounts were given as percentages (50%, 75% and 100%) of date palmwatering requirement (ETc). ETc was obtained from the means of theprevious thirty years, using CROPWAT4 WINDOWS. The performanceof the irrigation system was evaluated with reference to the applicationand storage efficiencies and distribution uniformity. The experiment wasorganized in a split plot design with three replicates. The irrigationsystems showed negative effect on distribution uniformity and positiveeffect on application and storage efficiencies. The locally made andimported bubblers revealed highly significant (P ≤0.01) differences withapplication and storage efficiencies, while there was no significantdifference between them. The 50% ETc recorded high significant valuesof application efficiency, but less values of storage efficiency anddistribution uniformity. Interaction of the irrigation systems and amountsof water showed positive effect, whereas locally made bubblers showedhigher values of application and storage efficiencies with 50% and 100%ETc, respectively. On the other hand, the basin irrigation system gavehighest values of distribution uniformity with 75% and 100% ETc .Hence,it was concluded that using bubbler irrigation system would give highirrigation efficiency, thus saving water for other agricultural activities.